Fuel for Conspiracy: Suspected Imperialist Plots and the Chaco War. Issue 1 (April 2019) - Roniger, Luis; Senkman, Leonardo
Conspiracy discourse interprets the world as the object of sinister machinations, rife with opaque plots and covert actors. With this frame, the war between Bolivia and Paraguay over the Northern Chaco region (1932–1935) emerges as a paradigmatic conflict that many in the Americas interpreted as resulting from the conspiracy manoeuvres of foreign oil interests to grab land supposedly rich in oil. At the heart of such interpretation, projected by those critical of the fratricidal war, were partial and extrapolated facts, which sidelined the weight of long-term disputes between these South American countries traumatised by previous international wars resulting in humiliating defeats and territorial losses, and thus prone to welcome warfare to bolster national pride and overcome the memory of past debacles. The article reconstructs the transnational diffusion of the conspiracy narrative that tilted political and intellectual imagination towards attributing the war to imperialist economic interests, downplaying the political agency of those involved. Analysis suggests that such transnational reception highlights a broader trend in the twentieth-century Latin American conspiracy discourse, stemming from the theorization of geopolitical marginality and the belief that political decision-making was shaped by the plots of hegemonic powers.